(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The emergence of Blockchain technology as Bitcoin, has completely transformed the process of exchanging financial capital, without an intermediary. The huge success of Bitcoin contributed to the rapid advancement and increase interest of the public in Blockchain technology. As people started digging more into the technology underlying Bitcoin, they started realizing that the blockchain capacity is not just confined to cryptocurrencies. It has the potential to impact a much wider domain of applications to solve many of the issues and challenges in real-world scenarios. One such scenario is product traceability in food supply chain (FSC). Traditional traceability systems are vulnerable to various issues and challenges such as lack of data transparency, confidentiality, centralized data storage, mistrust between the parties, product delay which needs to be addressed. This paper proposes a solution for product traceability in FSCs using Hyperledger Fabric (HLF), a permissioned blockchain framework. We keep a track of food products journey from source to destination. All the information associated with food products shipment recorded securely and immutably in a distributed ledger, which is sync and verified with all the participants in the FSC in real-time but can be accessed by the authorized participants only. For managing access rights to the blockchain network resources, access control rules are defined by embedding them in smart contracts. Moreover, REST API allows clients to interact with blockchain network is secured using, OAuth 2.0 authentication strategy. Finally, we evaluate the performance of the designed blockchain-based system for FSC.